Resistencia de la Resinas Híbrida, Nanohíbrida y Bulk Fill a la Fuerza de Compresión - Peñafiel Rodríguez, María Victoria (2019)
The aim of the present research is done to compare the resistance of the hybrid, nanohybrid and Bulk Fill resins to the compression force through laboratory studies and identify the resin that has the highest compressive strength. An observational, comparative, in vitro – experimental and cross – sectional study was applied, and 10 cylindrical specimens were named for the three groups with 4x4 mm measurements established in ISO 4049, observation was the technique, survey and the instruments the logbook and the questionnaire respectively. The trademarks used were Filtek Z250 3M as a hybrid, Filtek Z350 XT 3M as nanohybrid and Filtek Buk Fill 3M as Bulk Fill. The samples have been tasted of compressive strength of the metal cutting machine in the Materials Resistance Laboratory of the Metallurgical Metalworking Development Center of the Honorable Consejo Provincial of Tungurahua. The maxium compression effort achive were 162,998 MPa for Filtek Z250, 177,05 MPa for Filtek Z350 XT and 172,305 MPa for Filtek Bulk Fill. The statistical assessed determined a normal distribution of data, variable analysis (ANOVA) did not determine the final conclusion because there was not enough evidence to determine statistically significant differences between the groups, however, the descriptive statistics showed that the resin obtained greater resistance was the nanohybrid represented by the Filtek Z350XT.